Trend of cancer mortality of the female reproductive system in China from 2005 to 2018 and prediction to 2035: A log-linear regression and Bayesian age-period- cohort analysis - Lili Xu; Ting Zhao; Xin-hua Wang; Guang-sheng Wu; Weixia Nong (PLoS ONE, 2025)
Objective In recent years, the number of deaths from female reproductive system cancer in China has been continuously increasing, and there are relatively few studies on their mortality situation. This study aimed to analyze the mortality rate and its trend of the female reproductive system cancer in China from 2005 to 2018, to predict the situation until 2035, and to provide scientific basis for the prevention and control of the female reproductive system cancer in China. Methods The mortality rate latest data of the female reproductive system cancer was obtained from the Chinese Cancer Registry Annual Report from 2008 to 2021. Using the Joinpoint regression model, the annual percent change (APC) and average annual percentage change (AAPC) were calculated to describe the time trend. Age-period- cohort models were constructed to analyze the effects of age, period, and cohort. The study predicted the situation up to 2035 using a Bayesian age-period-cohort model. Result The age-standardized mortality rate (ASMR) of the female reproductive system cancer in China from 2005 to 2018 was 8.75/100,000, with rural areas being higher than urban areas. The mortality rate showed an upward trend from 2005 to 2018, with AAPC = 1.92% (95% CI: 1.68%, 2.16%). The growth trend in urban areas was more pronounced than that in rural areas, and the mortality risk was highest among the population aged 80–84 years. The period effect showed a trend of first increasing and then decreasing from 2005 to 2018, with the highest risk in the population born between 1990 and 1994. The mortality rate of the female reproductive system cancer in China will increase from 9.96/100,000 (95% CI: 9.37/100,000, 10.54/100,000) in 2019 to 11.98/100,000 (95% CI: 3.64/100,000, 20.31/100,000) in 2035. Conclusion The mortality rate of the female reproductive system cancer in China showed an upward trend from 2005 to 2018, and will continue to rise from 2019 to 2035. The female reproductive system cancer in China require continuous attention.